The impact of the financial crisis and natural catastrophes on CAT bonds - M. Gürtler; M. Hibbeln; C. Winkelvos (Technische Universität Braunschweig, Institut für Finanzwirtschaft, 2012)
CAT bonds are important instruments for the insurance of catastrophe risk. Due to a low degree of deal standardization, there is uncertainty about the determination of the CAT bond premium. In addition, it is not apparent how CAT bonds react after the financial crisis or a natural catastrophe. We empirically verify which factors determine the CAT bond premium and what effects arise if a catastrophe occurs. On a broad data set using secondary market premiums we find strong evidence that the recent financial crisis has a significant impact on CAT bond premiums. Furthermore, we find that after hurricane Katrina an increased risk perception for hurricanes can be observed.
Keywords: G01; G22; 330; CAT bonds; financial crisis; catastrophe events; risk premium